Comparison of efficacy, safety, and costs between neoadjuvant hypofractionated radiotherapy and conventionally fractionated radiotherapy for esophageal carcinoma. (22nd May 2019) - Lyu, Jiahua; Liu, Tao; Li, Tao; Li, Fang; Wang, Qifeng; Wang, Jie; Han, Yongtao; Wang, Junchao; Zhang, Jun; Peng, Lin; Lang, Jinyi
Abstract: Background: We compared the efficacy, safety, and costs of hypofractionated radiotherapy (HFRT) and conventional fractionated radiotherapy (CFRT) for the neoadjuvant treatment of esophageal cancer. Materials and Methods: Overall, 110 patients with esophageal cancer treated with neoadjuvant chemoradiotherapy from October 2002 to July 2017 were retrospectively included and divided into a HFRT group (42 patients received 30 Gray [Gy]/10 fractions for 2 weeks) and a CFRT group [68 patients received 40 Gy/20 fractions for 4 weeks]. Concurrent chemotherapy comprised cisplatin combined with either 5‐FU or taxane. Surgery was performed 3‐8 weeks after radiotherapy. We compared the outcomes, adverse events, and costs between the two groups. Results: Pathological downstaging was achieved in 78.6% of the HFRT group and 83.8% of the CFRT group ( P = 0.612). Compared with the CFRT group, the HFRT group had similar pathological complete response (pCR) (33.3% vs 35.3%; P = 0.834), median overall survival (OS) (40.8 months vs 44.9 months; P = 0.772) and progression free survival (32.7 months vs 35.4 months; P = 0.785). The perioperative complication rates were also similar between the groups, but the treatment time and costs were significantly reduced in the HFRT group ( P < 0.05). Finally, multivariate analysis identified cN0 stage, pathological downstaging and pCR as independent predictors of better OS. Conclusion: Preoperative HFRT is effective and safe for esophageal cancer. Moreover, it is similar to CFRT in terms of overall survival and toxicity and is cost effective and less time consuming. Abstract : This study compared the efficacy, safety, and costs of hypofractionated radiotherapy (HFRT) and conventional fractionated radiotherapy (CFRT) for the neoadjuvant treatment of esophageal cancer. We conclude that HFRT has comparable efficacy to CFRT without increasing adverse effect rates or decreasing the pathologic complete response, progression free survival or overall survival; therefore, it can be recommended as a safe and effective alternative to CFRT for neoadjuvant radiotherapy in patients with esophageal cancer. HFRT requires fewer fractions, can be delivered in a shorter duration and costs less when compared with CFRT.